As rendilheiras de bilros de Vila do Conde : como organizam o seu trabalho no presente relativamente ao passado - Lopes, Filipa (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article intends to outline, rather briefly, the way in which the bobbin lacemakers (rendilheiras de bilros) of Vila do Conde organise their work in the present in relation to the past, namely in what concerns the technology adopted, the organisation of production, the rights of ownership over the means of production and over production itself, their qualifications, their professional trajectories, their professional group, even their own socio-familial milieu and their relation to their work, stressing also the characterising elements of the work and the female workers.